HUBUNGAN MINAT BELAJAR DENGAN HASIL BELAJAR MATEMATIKA SISWA DI SMP NEGERI 3 TONDANO - Magenda, Trivona; Wenas, John Robby; Tilaar, Anetha L. F. (LPPM Politeknik Saint Paul Sorong, 2024)
The objective of this study was to explore the positive correlation between students' interest in learning and their mathematics achievement. A quantitative approach using a correlation method was applied, with the research conducted among seventh-grade students at SMP Negeri 3 Tondano. The study's population included all seventh-grade students, with a sample size of 44 participants. Data were gathered through questionnaires designed using a Likert scale to measure the students' level of interest. The hypothesis was tested through the Pearson Product Moment correlation method. The results indicated a significant positive relationship between students' interest in learning and their mathematics achievement, with a correlation coefficient of 0.7886, which falls under the strong correlation category.